IMPLEMENTASI WEB SERVICE UNTUK MOBILE COMMERCE - Suryadi, Grimaldi; Hiryanto, Lely; Tumbelaka, Bobby (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
E-commerce is currently widely used by companies to offer and provide information that can be in the form of products or services to quickly and accurately. In addition to quick and accurate, the information which stored in database must can be accessed anywhere and anytime. With the growth development of technology, the database can be accessed through mobile devices such as devices with Android operating system via Internet. In accessing the database from another device via Internet needed an interface or bridge that can be used and accessed by a wide variety of programming languages. Bridge or a interface is called a web service. With the existence of these technologies, e-commerce can be evolved into mobile e-commerce. Therefore 2 applications are made to support e-commerce which is web application and mobile application. Both applications show the products in accordance with the database of the company